1977
DOI: 10.1136/bjo.61.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Family distribution of concomitant squint in Greece.

Abstract: SUMMARY From a study of a large number of brothers and sisters suffering from concomitant squint, the following data were obtained: (1) 42-9 % of the patients showed congenital strabismus.(2) In 96 5 % of the sibs strabismus was of the same type. (3) The presence of a significant refractive error occurred in 82-8 % of the patients. (4) In all twins strabismus appeared at the same age in both twins, and the squint and the refractive error were of the same type. (5) The distance of the patients' homes from Athen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…This could be attributed to the impact of squint on the physical appearance of a female child with attendant psychological effect in future or the small sample size. Esotropia was the commonest type of squint like in many other similar reports 1,11,12 being the most common childhood squint. Though genetic predisposition has been associated with squint development, we didn't find much evidence of this in this study as only one of the patients was a twin and the first twin did not have squint.…”
Section: Discussionmentioning
confidence: 77%
“…This could be attributed to the impact of squint on the physical appearance of a female child with attendant psychological effect in future or the small sample size. Esotropia was the commonest type of squint like in many other similar reports 1,11,12 being the most common childhood squint. Though genetic predisposition has been associated with squint development, we didn't find much evidence of this in this study as only one of the patients was a twin and the first twin did not have squint.…”
Section: Discussionmentioning
confidence: 77%
“…It has long been known that eye misalignment tends to cluster in families (Jones, 1886), and recent studies have confirmed this fact for both phoria and strabismus (Abrahamsson, Magnusson & Sjostrand, 1999; Chimonidou, Palimeris, Koliopoulos & Velissaropoulos, 1977; Francois, 1961; Mash, Hegmann & Spivey, 1975; Paul & Hardage, 1994; Richter, 1967; Schlossman & Priestley, 1952; von Rotth, 1937). However, either genes or environment can contribute to resemblance among family members; therefore, familial clustering does not clarify etiology.…”
Section: Introductionmentioning
confidence: 95%
“…A large twin strabismus literature has accumulated (Chimonidou et al, 1977; de Decker & Feuerhake, 1978; DeVries & Houtman, 1979; Francois, 1961; Knobloch, Leavenworth, Bouchard & Eckert, 1985; Kondo, Mori & Adachi, 1975; Kvapilikova, 1969; Lang, 1990; Matsuo, Hayashi, Fujiwara, Yamane & Ohtsuki H, 2002; Orlebeke & Koole, 1999; Paul & Hardage, 1994; Podgor, Remaley & Chew, 1996; Reynolds & Wackerhagen, 1986; Richter, 1967; Schlossman & Priestley, 1952; Waardenburg, 1961; Weekers, Moureau, Hacourt & Andre, 1956; Wei, 1987). However, quantitative estimates of genetic and environmental influence have not yet been derived from these data, nor has this literature been evaluated in light of modern standards for twin research (Neale & Cardon, 1992; Rijsdijk & Sham, 2002; Sullivan, Kendler & Neale, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These heritability values are likely to be underestimates for the following three reasons: (i) Ϸ15-20% of strabismus is clearly associated with nonocular disorders, including low birth weight and global CNS defects (12), which are included in the population incidence in most studies; (ii) there is incomplete detection of esophorias and exophorias, microtropias, and the monofixation syndrome (reduced stereoacuity to worse than 60 s of arc), all of which occur at higher frequencies in families of strabismics and probably represent the incompletely penetrant phenotype (13,14); and (iii) similar or identical subtypes of strabismus tend to cluster within a single family and between monozygotic twins and this would lead to greater heritability estimates if strabismus subtypes were considered separately (15). As an example of the second point, Scott et al (14) found that the monofixation syndrome was present in 7.7% of first degree relatives of patients with infantile esotropia, compared with a prevalence of 1% in the general population.…”
mentioning
confidence: 99%